The Caves of Burnsville Cove, Virginia Fifty Years of Exploration and Science - White, William B (Springer, 2015)
This book highlights some of the most difficult and persistent exploration ever undertaken in the United States – in Burnsville Cove, a small limestone valley in west-central Virginia – while at the same time reviewing the scientific discoveries made in the area’s 116 km of caves in the course of 50 years. Overall, the book offers a unique combination of exploration and science by a conservation organization specifically dedicated to the preservation and study of the caves.